CO2-assisted fabrication of PLA foams with exceptional compressive property and heat resistance via introducing well-dispersed stereocomplex crystallites. (October 2022) - Cui, Weiwei; Wei, Xinyi; Luo, Jingyun; Xu, Bo; Zhou, Hongfu; Wang, Xiangdong
Abstract: Poly (lactic acid) (PLA) foams have been considered as one of the most promising and effective substitutes for traditional petroleum-based foams owing to their excellent biodegradability and biocompatibility. In order to enhance the compressive properties and heat resistance of PLA foams, ethylene-glycidyl methacrylate copolymer (EGMA) as a carrier was first blended with poly (D -lactic acid) (PDLA) to fabricate PDLA/EGMA masterbatches. Subsequently, the resultant masterbatches were added into poly (L -lactic acid) (PLLA) to obtain well-dispersed stereocomplex crystallites (SC). Finally, the obtained PLLA/EGMA/PDLA specimens were foamed using a confined batch foaming method with CO2 . The formation of SC was verified by X-ray diffraction and differential scanning calorimetry as well as their well dispersion was proven by scanning electron microscope and rheological measurement. Compared with pure PLLA, the melt viscoelasticity and crystallization rate of PLLA/EGMA/PDLA specimens were significantly improved by virtue of the formed well-dispersed SC. For PLLA/EGMA/PDLA foams, an ameliorated cell morphology was achieved. At a PDLA content of 6 wt%, the density-specific compressive strength and modulus of PLLA/EGMA/PDLA foams were 187 % and 360 % higher than those of pure PLLA foams, respectively. Additionally, the heat resistance of the PLLA/EGMA/PDLA foams was evidently enhanced, and their volume shrinkage was only around 1 % at 90 °C for 6 h. This study provides a prospect strategy for the preparation of lightweight, environmentally friendly, biodegradable PLA foams with satisfactory compressive performance and heat resistance. Highlights: PLLA/EGMA/PDLA foams were fabricated using a confined batch foaming method. PDLA/EGMA masterbatches was utilized to ameliorate the dispersion of the SC in PLA. Three orders of magnitude improvement in storage modulus of PLLA/EGMA/PDLA were achieved. The resultant PLLA/EGMA/PDLA foams exhibited improved compressive properties. The heat resistance of the PLLA/EGMA/PDLA foams was evidently enhanced.